(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
In this paper given and analysed are the factors related to the construction of motorways and having a negative impact on the environment. Given are the conditions o f the assessment of the impact of the motorways on the environment, arable land andforests and cultural heritage.